Financial Inclusion of Sharia Banking and Poverty 33 Province in Indonesia - Muhammad Nabil; Sri Herianingrum (ITB AAS INDONESIA Surakarta, 2022)
Through a conference held by the United Nations that produced the Sustainable Development Goals, poverty alleviation is the number one goal of seventeen goals. This study aims to look at the effect of Financial Inclusion in Islamic Banking and PDRB on Provincial Poverty 33 Province In Indonesia except North Borneo for Period 2014-2018. The financial inclusion indicator used in this study is the Islamic banking branch per 1000km2 as a dimension of access (BRNCH) and financing of Islamic banking to GDP Regional as a dimension of use (FNNC). Using a quantitative approach with panel data regression analysis techniques and random effect models as estimation models.The results of this study shows that there is a simultaneous significant effect between the inclusion of Islamic banking finance and GDP Regional on provincial poverty in Indonesia. While partially, the branch of Islamic banking per 1000 km2 does not have a significant effect on provincial poverty in Indonesia. GDP and Islamic banking financing towards GDP Regional have a significant negative effect on provincial poverty in Indonesia. this study examines the determinants of provincial poverty in Indonesia from the economic aspect. in future research, It is also necessary to consider and examine the dimensions of time and scope of research.